2000
DOI: 10.1121/1.428475
|View full text |Cite
|
Sign up to set email alerts
|

Backscattering enhancements associated with subsonic Rayleigh waves on polymer spheres in water: Observation and modeling for acrylic spheres

Abstract: Unlike most common solids, "plastic" polymer solids typically have shear and Rayleigh wave phase velocities less than the speed of sound in water. Subsonic Rayleigh waves on smooth objects in water are not classified as leakey waves and it is necessary to reexamine backscattering mechanisms. Also the intrinsic material dissipation of the Rayleigh wave can be significant. Backscattering by acrylic or polymethlmethacrylate (PMMA) spheres in water is analyzed and measured in the region ka = 1.5-7 and it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…More detailed discussions about the abovementioned vibrational modes and their lifetime can be found in the literature. [24][25][26][27][28][29][30] In the case of solid elastic materials, these eigenfrequencies (poles), generally, fall into two main categories depending on whether their phase velocities lie close to the elastic bulk wave speeds in the solid, i.e., Rayleigh (l ¼ 1) and Whispering-gallery type modes l ¼ 2, 3,…, or to the acoustic wave speed in the fluid, i.e., Franz-type creeping modes. The modes in the first category are due to the resonances of internal waves and usually close to the real frequency axis (i.e., slightly attenuated), and therefore their effects are more visible in form-function spectra, whereas the Franz creeping modes spin the surface of the sphere's circumference with successively increasing integer numbers of wavelength and are highly attenuated and thus their effects are hard to detect.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed discussions about the abovementioned vibrational modes and their lifetime can be found in the literature. [24][25][26][27][28][29][30] In the case of solid elastic materials, these eigenfrequencies (poles), generally, fall into two main categories depending on whether their phase velocities lie close to the elastic bulk wave speeds in the solid, i.e., Rayleigh (l ¼ 1) and Whispering-gallery type modes l ¼ 2, 3,…, or to the acoustic wave speed in the fluid, i.e., Franz-type creeping modes. The modes in the first category are due to the resonances of internal waves and usually close to the real frequency axis (i.e., slightly attenuated), and therefore their effects are more visible in form-function spectra, whereas the Franz creeping modes spin the surface of the sphere's circumference with successively increasing integer numbers of wavelength and are highly attenuated and thus their effects are hard to detect.…”
Section: à3mentioning
confidence: 99%
“…25 The complex eigenfrequencies can be defined by X n;l ¼ a n;l À 1 2 iC n;l , where n ¼ 0,1,2,… specifies the fundamental frequency and l ¼ 1,2,3,…, identifies the overtones associated with the fundamental mode of the vibration the members of which appear in all the partial waves, shifting to higher frequencies from one partial wave to the next. [24][25][26][27][28][29][30] The quantity C n;l shows the distance of the resonance to the real axis, and C n;l ð Þ À1 is a measure of the lifetime of the resonance. More detailed discussions about the abovementioned vibrational modes and their lifetime can be found in the literature.…”
Section: à3mentioning
confidence: 99%
“…The study of sound scattered by a fixed solid sphere is a classic but continuing area of study and difficulties arise in the interpretation of observed phenomena especially when trying to deal with elasticity and absorption 14,15,16 .…”
Section: Scattering By An Elastic Spherementioning
confidence: 99%
“…Physically, f represents the sum of the specular echo and of interferences due to the radiation by Rayleigh waves 15,16 . As a result, f is a strongly varying function, particularly for high values of ka.…”
Section: Scattering By An Elastic Spherementioning
confidence: 99%
“…RST has been actively studied in the aim of identifying targets from resonances in their echoes [9]. A number of models have been developed which gave accurate determination of the magnitude of the backscattered signals [1,[10][11][12][13][14][15][16]. Another quantity of equal interest is the phase of the backscattered signals since, in some situations, many of the important features of an echo signal are preserved only if the phase is retained.…”
Section: Introductionmentioning
confidence: 99%